2010
DOI: 10.1177/1538574410376601
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Foot Collateral Vessels on Ulcer Healing and Limb Salvage After Successful Endovascular and Surgical Distal Procedures According to an Angiosome Model

Abstract: Ulcer blood flow restoration through collateral vessels may give similar results to those obtained through its specific source artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
195
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(205 citation statements)
references
References 28 publications
7
195
0
3
Order By: Relevance
“…In 203 consecutive patients with CLI treated endovascularly, Iida et al [38] reported 86 % of limb salvage rate in the DR group compared to 69 % in the IR group. Similar results were reported by Varela et al [39] and by Alexandrescu et al [40], documenting how the treatment of diabetic patients with CLI throughout DR provide better results in terms of limb salvage and ulcer healing than IR.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In 203 consecutive patients with CLI treated endovascularly, Iida et al [38] reported 86 % of limb salvage rate in the DR group compared to 69 % in the IR group. Similar results were reported by Varela et al [39] and by Alexandrescu et al [40], documenting how the treatment of diabetic patients with CLI throughout DR provide better results in terms of limb salvage and ulcer healing than IR.…”
Section: Discussionsupporting
confidence: 86%
“…At our institute, the first treatment option is DR, a strategy that is in line with data from the literature [37][38][39][40]. Only in cases of technical impossibility of DR do we turn to our second choice, the indirect approach.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The concept delineates the human body in specific 3D blocks of tissue, fed by peculiar arterial and venous bundles of blood supply (Attinger et al, 2001(Attinger et al, , 2006Taylor et al, 1990Taylor et al, , 1998. Originally pioneered for the pediculated flaps techniques, the AM strategy (Attinger et al, 2006;Taylor et al, 1998) was also applied to improve healing in lower limb ischemic ulcers (Alexandrescu et al, 2008;Neville et al, 2009;Varela et al, 2010;Setacci et al, 2010). Based on the anatomical studies of Taylor (Taylor et al, 1990(Taylor et al, , 1998 and Attinger (Attinger et al, 2001(Attinger et al, , 2006, new preferential strategies for vascular access, revascularization or amputation were described.…”
Section: Discussionmentioning
confidence: 99%